Private Rome: Private #18 - Patterson, James, 1947-; Hamdy, Adam, 1974- (London : Century, 2023)
Secrets, lies and murder in the heart of the Vatican. The thrilling new instalment in the Private series. A priest is murdered and a Private agent is the number one suspect. Jack Morgan is in Rome celebrating the opening of the new local Private office, when the party takes a deadly turn. Private agent Matteo Ricci is found at the party standing over the body of a dead priest with a gun in hand, swearing he did not kill the man. As Jack tries to prove Matteo's innocence, he uncovers a much deadlier conspiracy - which leads straight to the heart of the Vatican. With corruption closing in on all sides, Jack must decide who he can trust before the city falls.
new book 2024 winter.
Keywords: Morgan, Jack -- (Fictitious character) -- Fiction; Private (Imaginary organization) -- Fiction; Private investigators -- Fiction; Private security services -- Fiction; Murder -- Investigation -- Fiction; Conspiracies -- Fiction; Secrecy -- Fiction; Corruption -- Fiction; Thriller fiction